Exporters and credit constraints. A firm-level approach - Mirabelle Muûls (National Bank of Belgium, 2008)
By building a theoretical model and taking it to the data with two novel datasets, this paper analyses the interaction between credit constraints and exporting behaviour. Building a heterogeneous firms model of international trade with liquidity-constrained firms yields several predictions on the equilibrium relationships between productivity, credit constraints and exports that are then verified in the data. The main findings of the paper are that firms are more likely to be exporting if they enjoy higher productivity levels and lower credit constraints. Also, credit constraints are important in determining the extensive but not the intensive margin of trade in terms of destinations. This introduces a pecking order of trade. Finally, an exchange rate appreciation will cause existing exporters to reduce their exports, entry of credit-constrained potential exporters and exit of the least productive exporters
Keywords: D92; F10; F36; G28; 330; Credit constraints; heterogeneous firms; margins of export; export destinations; exchange rates and trade; Liquiditätsbeschränkung; Außenhandelsfinanzierung; Exportwirtschaft; Wechselkurs; Theorie; Belgien